The Role of the Immune System in Maintaining the Constancy of the Internal Environment of the Body - Shaukatovna, Ismatova Marguba; Ikromovna, Nasimova Diyora (American Journal of Biomedicine and Pharmacy, 2025)
The immune system plays a fundamental role in preserving the stability and constancy of the body’s internal environment, a process known as homeostasis. It protects the organism from harmful pathogens, foreign substances, and internal abnormalities such as malignant cells. Through a complex network of cells, tissues, and signaling molecules, the immune system continuously monitors the body, identifying and eliminating threats while maintaining tolerance to self-antigens. This article explores the physiological mechanisms of immune regulation in maintaining homeostasis, focusing on innate and adaptive immunity, cytokine signaling, and immune tolerance. The research highlights how disturbances in immune balance can lead to pathological conditions such as autoimmune diseases, allergies, and immunodeficiency, emphasizing the immune system’s central role in overall health and homeostatic equilibrium. The immune system is the key physiological mechanism that ensures the balance and stability of the human body by protecting it from external and internal threats. It performs a complex network of functions that include recognition, neutralization, and elimination of pathogenic microorganisms, abnormal cells, and toxic substances while maintaining tolerance toward the body’s own tissues. This article discusses how the immune system maintains homeostatic balance, analyzes the functional interaction between innate and adaptive immunity, and describes how the dysregulation of immune responses leads to various pathological processes. The immune system, acting as a self-regulating defense mechanism, constantly monitors the internal environment, adjusts immune responses according to the body’s needs, and restores equilibrium after infection, injury, or stress.